Early detection of skin cancer by skin self‐examination. (3rd June 2019) - Ersser, S.J.; Effah, A.; Dyson, J.; Kellar, I.; Thomas, S.; McNichol, E.; Caperon, E.; Hewitt, C.; Muinonen‐Martin, A.J.
Summary: Skin cancer is increasing in many countries, including in the UK. For example, in the USA in 2017, over 87, 000 people had been diagnosed with a dangerous type of skin cancer (melanoma); of these it was expected that nearly 10, 000 would die from the condition. We are a U.K based research team that conducted a review of scientific papers from across the world. Our aim was to examine and pool the existing research on whether the different approaches to helping people to examine their own skin, to detect skin cancer early, are effective or not. This review identified all the relevant published articles for available research studies up to April 2018. The identified relevant studies totalled 18 in number, which we then summarised. These approaches included education, such as teaching and reminding people (sometimes using technology, for example, using computers and mobile phones) to examine their skin and quickly report any suspicious changes to their doctor. We found that the various approaches used had a positive effect on peoples' likelihood and ability to examine their skin, especially in the short‐term. More studies targeted people at higher risk of skin cancer, such as those with a previous diagnosis of skin cancer, compared to people at no greater risk. Of the research we looked at, two thirds of the studies were poorly designed. Skin specialists should raise awareness and support people to routinely examine their skin for skin cancer, especially those at high risk. Abstract : Linked Article: Ersser et al. Br J Dermatol 2019; 180 :1339–1347